Plasma Renin in ipsilateral renal vein in patients with chronic unilateral pelvic ureteric junction obstruction (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):543-8The abstract of this article is available on the PubMed website